Emotive and cognitive processes in cancer patients: linguistic profiles of post‐traumatic growth. (6th January 2017) - Scrignaro, M.; Marini, E.; Magrin, M.E.; Borreani, C.
Abstract : Starting from the challenge offered by the authors of the post‐traumatic growth (PTG) construct (Tedeschi & Calhoun, 2004 ), this paper aims to explore the existence of different linguistic profiles of cognitive and emotional processes in PTG narratives. The autobiographical narratives of 40 cancer patients were analysed for both PTG and linguistic indicators of emotions and cognitive processes. PTG was operationalised as the presence of redemption sequences (McAdams, 2001 ). The emotional and cognitive linguistic indicators were analysed by the LIWC program (Pennebaker & Francis, 1999 ). All the narratives included PTG ( M  = 3.55, SD  = 1.91). Three clusters of linguistic profiles were retained (60%–79% of variance explained): "disengagement", "assimilative" and "accommodative". These clusters differed significantly by PTG ( F  = 9.70, p  < .000, η 2  = .34). Given the limitations of the study, the results highlight the importance of the linguistic approach to a deeper understanding of PTG and to tailored pathways of its promotion.